2020
DOI: 10.1007/s11764-020-00913-8
|View full text |Cite
|
Sign up to set email alerts
|

Persistent digital divide in health-related internet use among cancer survivors: findings from the Health Information National Trends Survey, 2003–2018

Abstract: Purpose Prior research on the use of the internet among cancer survivors indicates a digital divide. The online landscape and patterns of information consumption, however, have notably changed over the past decade necessitating an updated examination of health-related internet use (HRIU) among cancer survivors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
50
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 57 publications
(73 reference statements)
7
50
4
Order By: Relevance
“…These differences may be attributable to differences in health literacy, difficulties and frustration in accessing online information, or trust in health information from online sources [ 23 , 24 , 27 , 45 , 46 , 47 , 48 , 49 , 50 ]. Consistent with previous studies, we observed that older adults were also less likely to use the internet to locate health-related information for themselves or others [ 13 , 20 , 23 , 27 , 46 ]. Prior studies have observed that older individuals are more likely to access and trust health information from other sources, including friends and families and religious organizations [ 20 , 27 , 49 ].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…These differences may be attributable to differences in health literacy, difficulties and frustration in accessing online information, or trust in health information from online sources [ 23 , 24 , 27 , 45 , 46 , 47 , 48 , 49 , 50 ]. Consistent with previous studies, we observed that older adults were also less likely to use the internet to locate health-related information for themselves or others [ 13 , 20 , 23 , 27 , 46 ]. Prior studies have observed that older individuals are more likely to access and trust health information from other sources, including friends and families and religious organizations [ 20 , 27 , 49 ].…”
Section: Discussionsupporting
confidence: 91%
“…Each observation with missing data was imputed 20 times and the imputed weight was recalibrated to preserve the national representative survey weight. Given previous HINTS studies examining differences in eHealth use among smokers and cancer survivors, all models were adjusted for smoking status, personal cancer history, and family cancer history [ 13 , 25 , 35 , 36 , 37 , 38 , 39 , 40 ]. To measure the change in eHealth usage in different HINTS release, a dummy variable was used to represent the survey year.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These access issues are likely to have a substantial impact on the uptake of e-health interventions. Furthermore, studies have shown that older adults are less likely to use the Internet, to be users of mobile health apps, and to seek cancer information online [ 9 , 17 , 18 ]. This suggests there are also likely to be issues with long-term engagement in this age group, as they may be less familiar or comfortable with using e-health interventions or accessing information online.…”
Section: Introductionmentioning
confidence: 99%